Systematic Literature Review: Nilai-nilai Pendidikan dalam Kewirausahaan Islam: Systematic Literature Review: Educational Values in Islamic Entrepreneurship - Lestari, Sinta; Nurpriatna, Ade; Hasanah, E.; Ismatullah, Ade; Malik, Muhammad Ibnu (Risalah Kharisma, 2024)
This study addresses the rising unemployment rate among vocational graduates in Sukabumi, Indonesia, by exploring the integration of Islamic values into entrepreneurship education. The core issue lies in the mismatch between graduates’ skills and labor market needs, compounded by insufficient emphasis on ethical entrepreneurship in Islamic institutions. Through a systematic literature review, this research analyzes how Islamic principles honesty (sidq), trustworthiness (amanah), justice (‘adl), and excellence (ihsan) can create sustainable, ethical businesses. Data were extracted from Scopus, Google Scholar, and peer-reviewed journals (2014–2024) using keywords like "Islamic entrepreneurship" and "halal business." Results demonstrate that these values strengthen customer trust, operational transparency, and long-term business resilience while fostering socio-economic equity. The study concludes that embedding Islamic ethics into vocational curricula can cultivate entrepreneurial graduates who balance profit with social impact. Practical implications include policy recommendations for enhancing Islamic entrepreneurship programs and addressing ethical gaps in modern business practices. This research contributes to the discourse on faith-based entrepreneurship and offers a framework for aligning education with market demands.